The impact of board composition on shareholder wealth creation: evidence from public companies in Sri Lanka - M. S. A. Riyad Rooly (Journal of Enterprise and Development (JED), 2022)
Purpose — This research aims to examine the impact of board composition on shareholder wealth in line with the agency and resource dependency theory approach due to the poor corporate governance practices leading to investors' lack of confidence. Method — The study samples included companies listed on the Colombo Stock Exchange in Sri Lanka. The banks and financial institutions were excluded from this study. The study period consists of seven years, and a final sample of 175 companies was selected for the analysis. E-View 9 statistical software was used to test the association between Board composition-related variables and shareholder wealth. Result — The findings revealed that board size, separate leadership structure, and proportion of non-executive directors on the Board positively influence shareholder wealth. At the same time, a separate leadership structure also tends to enhance the shareholder wealth of companies. It is noted that a large board and a higher proportion of non-executive directors on the Board would benefit shareholders, which supports the theoretical prediction of agency and resource dependency theories and the code of best practices on corporate governance in Sri Lanka. The result related to women's representation on the Board does not significantly influence shareholder wealth since the gender balance was not prioritized in Sri Lankan listed companies. Recommendation — The findings provide valuable information to professionals and policymakers to develop a framework for corporate governance systems. It is also advisable to consider the gender balance on board affairs. Corporate governance mechanisms are considered important factors in protecting shareholder interests at large. Contribution — There were few studies in Sri Lanka that specifically examined corporate governance best practices and their impact on firm performance, but no single study directly addresses the shareholder wealth of listed companies in Sri Lanka. This study is intended to fill in this gap.